A case of juvenile polymyositis post viral hepatitis A - Samuel, Hanock Unni; Jayachandran, N. V.; Thulaseedharan, N. K. (International Journal of Advances in Medicine, 2017)
Polymyositis is rare as a stand-alone entity and is often misdiagnosed; most patients whose condition has been diagnosed as polymyositis have inclusion-body myositis, necrotizing autoimmune myositis, or inflammatory dystrophy. Polymyositis remains a diagnosis of exclusion and is best defined as a subacute proximal myopathy in adults who do not have rash, a family history of neuromuscular disease, exposure to myotoxic drugs (e.g. statins, penicillamine, and zidovudine), involvement of facial and extraocular muscles, endocrinopathy, or the clinical phenotype of inclusion body myositis. The etiology of polymyositis may be due to underlying systemic autoimmune diseases, viral, parasitic, bacterial infections or drug induced. Here we describe a case of juvenile polymyositis post viral infection with hepatitis A.